Does leverage fit non-performing loans in the COVID-19 pandemic – evidence from the Vietnamese banking system - Nguyen Kim Quoc Trung (Cogent Business & Management, 2022)
The study aims to estimate the effect of leverage on non-performing loans in Vietnamese commercial banks from 2010 to 2020. This article uses qualitative (expert interviews, namely senior credit officers' and credit managers' surveys to find out the expert consensus coefficient) and quantitative research methods (Generalized Method of Moments to solve the endogeneity). The findings show that leverage is a statistically significant factor and negatively affects non-performing loans. In line with corporate governance theories, such as agency theory and stakeholder theory, this study emphasizes the significant role of the leverage ratio in dealing with non-performing loans at commercial banks in Vietnam during the COVID-19 pandemic. Besides, the study also highlights effective mechanisms to control and mitigate non-performing loans in the credit granting process.
Keywords: G21; M10; H81; 650; COVID-19; Vietnam; non-performing loans; commercial banks; leverage ratio; SGMM